Re-Desain Gereja Katolik Santo Paulus Di Surabaya Berdasarkan Ajaran Allah Tritunggal - Sriti Mayang Sari, Frederick Irianto Tantu (Intra, 2014)
St. Paul Catholic Church is one of the Catholic Churches in Surabaya. This church located on the complex of Navy Juanda, on Juanda-Waru street. Trinity is one of the main doctrine in Catholic : the God in three persons : Father, Son, and Holy Spirit. In this design work, writer makes a new interior design for this church which supposed to give an illustration about Catholicâ doctrine : The Trinity. The interior that based on doctrine means that the design will reflect the presents of God Trinity, direct or indirect - through the churchâs interior. So this design can introducing the Catholic doctrine to society, specially to give comprehension for the Catholic people.